2010
DOI: 10.1074/jbc.m110.162933
|View full text |Cite
|
Sign up to set email alerts
|

Human Alveolar Type II Cells Secrete and Absorb Liquid in Response to Local Nucleotide Signaling

Abstract: A balance sheet describing the integrated homeostasis of secretion, absorption, and surface movement of liquids on pulmonary surfaces has remained elusive. It remains unclear whether the alveolus exhibits an intra-alveolar ion/liquid transport physiology or whether it secretes ions/liquid that may communicate with airway surfaces. Studies employing isolated human alveolar type II (AT2) cells were utilized to investigate this question. Human AT2 cells exhibited both epithelial Na

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
91
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 63 publications
10
91
0
Order By: Relevance
“…5A). This is 308 similar to what the Boucher group found in the primary human cells (Bove et al, 2010). In 309 the meantime, treatment with 1 mM ouabain could decrease the TEPD to 71.89% ( Figure. 310 5B).…”
Section: Effect Of Inhibitors On the Ion Transport 305supporting
confidence: 78%
See 2 more Smart Citations
“…5A). This is 308 similar to what the Boucher group found in the primary human cells (Bove et al, 2010). In 309 the meantime, treatment with 1 mM ouabain could decrease the TEPD to 71.89% ( Figure. 310 5B).…”
Section: Effect Of Inhibitors On the Ion Transport 305supporting
confidence: 78%
“…In contrast, the Boucher group found that CFTR secretes Cl -in the primary 313 human cells at baseline (Bove et al, 2010). We found other Cl -channels were expressed at 314 mRNA level in the H441 cells under AMC conditions (data not shown), so a broad spectrum 315…”
Section: Effect Of Inhibitors On the Ion Transport 305mentioning
confidence: 66%
See 1 more Smart Citation
“…The aqueous lining layer height in the lung parenchyma is very thin, i.e. about 5 m as reported for primary human epithelial type II cells in culture [27], therefore, the volume is also very small and makes it difficult to collect it in vitro or in vivo to determine the colloidal behavior of NP in this liquid. An alternative approach is to use artificial alveolar fluid, and it has been shown that incubation of this liquid with silver NPs induces aggregation Fig.…”
Section: Mucusmentioning
confidence: 99%
“…Influenzainfected mice developed decreased Na + reabsorption and increased Cl − secretion across their alveolar epithelium in vivo (11). Cl − secretion has also been shown in confluent monolayers of rat and human alveolar epithelial type II (ATII) cells in the presence of amiloride (to block ENaC) and forskolin (to activate the CFTR) (15,16). Finally, studies of small airways using a miniature Ussing chamber system showed a switch from Cl − absorption to secretion through CFTR when Na + transport was inhibited by amiloride (17).…”
mentioning
confidence: 99%